Alley cropping for food crop production in the humid and subhumid tropics - Kang, B.; Van der Kruijs, A.C.M.B.; Couper, D.C. (1989)
Upland arable farming on fragile, tropical soils requires viable, sustainable, and environmentally sound prod uction systems that can meet the requirements of farmers who use traditional cultivation practices. Alley cropping, a scale-neutral technology, offers one of the best potentials for sustainable agriculture. Trials where various crops were grown between Gliricidia sepium and Leucaena leucocephala tree rows in the lowland humid and subhumid tropics on nonacid soils have shown good results. Prunings from selected leguminous woody species such as Leucaena and Gliricidia give high nitrogen yield; these species also assist nutrient cycling. Prunings from woody species can also improve and maintain the organic matter, nutrient status, and biological activity of the soil. Results from long-term plots showed that maize yield was higher in alley-cropping plots than in control plots, even with the application of nitrogen. Cassia siamea and Acioa barterli are promising crops for alley farming on acid soils. The inclusion of hedgerows reduced runoff and erosion. Mechanized alley cropping is feasible if managed properly